Combined Gamma Conglutin and Lupanine Treatment Exhibits In Vivo an Enhanced Antidiabetic Effect by Modulating the Liver Gene Expression Profile - Paloma Lucía Guerra-Ávila; Tereso J. Guzmán; José Alfredo Domínguez-Rosales; Pedro Macedonio García-López; Alejandra Beatriz Cervantes-Garduño; Michael Wink; Carmen Magdalena Gurrola-Díaz (MDPI AG, 2023)
Previous studies have individually shown the antidiabetic potential of gamma conglutin (Cγ) and lupanine from lupins. Until now, the influence of combining both compounds and the effective dose of the combination have not been assessed. Moreover, the resulting gene expression profile from this novel combination remains to be explored. Therefore, we aimed to evaluate different dose combinations of Cγ and lupanine by the oral glucose tolerance test (OGTT) to identify the higher antidiabetic effect on a T2D rat model. Later, we administered the selected dose combination during a week. Lastly, we evaluated biochemical parameters and liver gene expression profile using DNA microarrays and bioinformatic analysis. We found that the combination of 28 mg/kg BW Cγ + 20 mg/kg BW lupanine significantly reduced glycemia and lipid levels. Moreover, this treatment positively influenced the expression of Pdk4, G6pc, Foxo1, Foxo3, Ppargc1a, Serpine1, Myc, Slc37a4, Irs2, and Igfbp1 genes. The biological processes associated with these genes are oxidative stress, apoptosis regulation, and glucose and fatty-acid homeostasis. For the first time, we report the beneficial in vivo effect of the combination of two functional lupin compounds. Nevertheless, further studies are needed to investigate the pharmacokinetics and pharmacodynamics of the Cγ + lupanine combined treatment.